2018
DOI: 10.1016/j.otsr.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic anterior shoulder instability with significant Hill–Sachs lesion: Arthroscopic Bankart with remplissage versus open Latarjet procedure

Abstract: III; comparative retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 28 publications
3
46
0
3
Order By: Relevance
“…There was no difference at one year between patients who underwent surgery on an outpatient or inpatient basis. Besides, the clinical results of both groups according to persistent pain and apprehension and loss of external rotation were similar to what was already reported in the literature [5][6][7][8][9]. The use of interscalene block with long-acting local anesthetic is a well-accepted approach that produces 8 to 12 hours of postoperative analgesia [10].…”
Section: Discussionsupporting
confidence: 81%
“…There was no difference at one year between patients who underwent surgery on an outpatient or inpatient basis. Besides, the clinical results of both groups according to persistent pain and apprehension and loss of external rotation were similar to what was already reported in the literature [5][6][7][8][9]. The use of interscalene block with long-acting local anesthetic is a well-accepted approach that produces 8 to 12 hours of postoperative analgesia [10].…”
Section: Discussionsupporting
confidence: 81%
“…The failure rate of closed reduction was high due to soft tissue obstruction (long head of biceps, intra-glenoid scar, or posterior capsular contracture) and osseous block (glenoid fractures or engaging Hill-Sachs lesions), meanwhile the danger of an iatrogenic fracture or neurovascular damage was also high 8,22 . The pathophysiological changes of the chronic anterior shoulder dislocation were different from those of recurrent anterior dislocation, which also limited the application of arthroscopy 6,23,24 . In this study, the duration of dislocation was more than 3 weeks in all cases, and all patients underwent open reduction and stabilization of the involved shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the post‐RTSA instability had two distinct etiologies: (i) instability due to inadequate soft tissue tensioning and/or axillary nerve palsy; and (ii) instability due to impingement or liner failure. Bah et al 24 . compared arthroscopic Bankart with remplissage with open Latarjet procedure for chronic anterior shoulder instability with significant Hill–Sachs lesion.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 For many surgeons, the amount of glenoid and humeral bone loss in this study's patient population would encourage additional stabilizing measures in the form of Latarjet or Bankart repair with the addition of remplissage (the debate wears on). [10][11][12] Thus, another way to interpret the potential value anterior glenoid cartilage curettage is as an additional tool when treating patients in subcritical bone loss. Perhaps removing 5 mm of glenoid cartilage allows for anchor placement further posterior on the glenoid face, thus further closing off of the anterior glenohumeral joint space while providing potential added biologic benefit of increased bone to capsulolabral apposition.…”
Section: See Related Article On Page 837mentioning
confidence: 99%